2004
DOI: 10.1136/jcp.2003.007138
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid transcription factor 1 in pulmonary adenocarcinoma

Abstract: Aims: To discover whether variations in thyroid transcription factor 1 (TTF-1) staining in different subtypes and patterns of pulmonary adenocarcinoma are related to the putative origin of the tumour. In addition, to confirm the specificity of TTF-1 for pulmonary (as opposed to other sites) adenocarcinoma, to examine the possible prognostic relevance of TTF-1 positivity in lung cancer, and to review this laboratory's experience of TTF-1 in diagnostic practice. Materials/Methods: In total, 128 primary lung aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
123
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 34 publications
(26 reference statements)
10
123
2
1
Order By: Relevance
“…Some mentions of non-terminal respiratory unit type adenocarcinoma or central bronchial adenocarcinoma have been made. [7][8][9][10] An old study by Edwards 8 suggested three subtypes of adenocarcinoma according to its location: groups I to III. Group I was designated as parenchymal adenocarcinoma and group II as bronchial adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some mentions of non-terminal respiratory unit type adenocarcinoma or central bronchial adenocarcinoma have been made. [7][8][9][10] An old study by Edwards 8 suggested three subtypes of adenocarcinoma according to its location: groups I to III. Group I was designated as parenchymal adenocarcinoma and group II as bronchial adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have focused on this issue. [5][6][7][8][9][10] Recently, peripheral adenocarcinoma has been defined as terminal respiratory unit adenocarcinoma. [11][12][13] Their clinicopathological characteristics are generally well defined.…”
mentioning
confidence: 99%
“…For example, thyroid transcription factor 1 (TITF1) in the novel hotspot at 14q12-q13 is known to be overexpressed specifically in lung adenocarcinoma, the predominate subtype of NSCLC from which the 27 cell lines in our study were derived (Fabbro et al, 1996). This gene encodes a homeodomain transcription factor that is involved in regulating pulmonary development and gene expression (Apergis et al, 1998) and has been proposed to be a lineage marker for tumors arising from the peripheral airway (Stenhouse et al, 2004). Adenocarcinomas that express TITF1 are dependent on its persistent expression for survival (Tanaka et al, 2007).…”
Section: Existence Of An Amplifier Phenotypementioning
confidence: 99%
“…Carcinomas arising from lung and thyroid also show frequent TTF-1 expression. 1,2 As the lung is one of the most common sites of metastasis, TTF-1 is considered as a reliable marker to distinguish between primary lung carcinoma and lung metastasis, especially when dealing with an adenocarcinoma or a large-cell carcinoma. [3][4][5][6] It is also considered as a reliable marker in the differential diagnosis between pleural localization of lung origin carcinoma and malignant mesothelioma.…”
mentioning
confidence: 99%